Trade and Investment in the Greater Mekong Subregion: Remaining Challenges and the Unfinished Policy Agenda - Jayant Menon; Anna Cassandra Melendez (Asian Development Bank (ADB), 2011)
The Greater Mekong Subregion (GMS) is one of the most successful stories of economic transition and integration among developing countries. Strong rates of economic growth since the early 1990s have been fueled by increased trade and foreign direct investment (FDI) in the subregion. This economic progress has translated into marked improvements in living standards and human development outcomes, and dramatic reductions in poverty. Unilateral policy reforms and greater economic cooperation through the GMS Program in particular have led to positive trade and investment growth. More recently, membership in the World Trade Organization (WTO) and participation in the Association of Southeast Asian Nations (ASEAN) Free Trade Agreement (AFTA) and other preferential trading agreements have driven reforms. Despite these achievements, the trade policy reform agenda remains incomplete. It is important for the GMS members of AFTA to multilateralize their preferences in order to avoid trade diversion and deflection, and remain open to global trade. This should also be the objective of the various ASEAN+1 bilateral free trade agreements (FTAs). Retaining a multiple-tier tariff system is unlikely to mitigate revenue loss, but could unnecessarily burden an already stretched bureaucracy, or lead to more rent-seeking. In order to reduce vulnerability to external shocks, diversification of both export commodities and markets are being considered. Intra-sectoral diversification of export commodities is likely to be more viable and less costly than inter-sectoral diversification. It is unlikely, however, that any rebalancing of growth from foreign to domestic demand would be required in the GMS countries in order to increase resilience to external shocks.
hdl:11540/2030
Keywords: F15; F59; O53; 330; Greater Mekong Subregion (GMS); Cambodia; the Lao People's Democratic Republic (Lao PDR); Myanmar; Thailand; Viet Nam; trade and investment; regional economic integration; regional trade agreements; economic diversification